Aesthetic Experience, Investigation, and Classic Ground: Responses to Etna from the First Century CE to 1773. (31st December 2020) - Hollis, Dawn
In 1773, the Scottish traveller Patrick Brydone published an account of visiting Mount Etna, in which he drew on three distinct categories of thought: the scientific, the aesthetic, and the cultural. He carried his barometer up the volcano to measure it; he was overwhelmed with awe on viewing the sunrise from its summit; and he carefully set his account in the context of different mythological and philosophical explanations of Etna, largely drawn from the writings of classical authors. In preceding centuries, Thomas Burnet's Theory of the Earth (1690) and Athanasius Kircher's Mundus Subterraneus (as presented in a 1669 English translation) viewed mountains as laboratories for better understanding nature, for evoking a sense of eschatological awe, and as embedded in long traditions of cultural appreciation. Earlier still, Pietro Bembo in 1496 recounted his journey to the summit of Etna which wove together personal observation, classical insights, and aesthetic admiration. In an ancient example, the first-century anonymous Aetna poem urged readers to move beyond mythological explanations for volcanic activity and to instead enjoy true aesthetic pleasure in investigating the volcano and its causes for themselves. This article offers a close reading of these texts in order to demonstrate three key points. The first is that an intense aesthetic experience of volcanoes can be found in accounts predating the eighteenth-century articulation of the 'natural sublime'. The second is that the compulsion to investigate and understand natural phenomena, as a key element of aesthetic appreciation, is also evident before the Enlightenment. Third, the article suggests that a sense of Etna as 'classic ground' – as a feature which both intensified the viewer's interest in its natural phenomena and produced an 'interested' aesthetic experience of its natural greatness – likewise extends back even to the ancient texts from which later travellers would draw their own cultural associations.